TUMBUHAN TERATAI SEBAGAI IDE PENCIPTAAN PERHIASAN PADUAN PERAK DAN KAYU - Lilik Istria Ari; Ari Supriyanto (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2018)
This artistic research aims to (1) carry out exploration of designs with lotus plant ideas, (2) realize jewelry works based on selected designs that have been designed. The works produced are lotus-themed jewelry. Lotus plants not only have beauty but also philosophical and great benefits for humans. Lotus is a sacred plant for Hindu-Buddhist religion. Even for some countries lotus plants are used as a symbol of the country which means purity, humility, as well as a symbol of God. The process of making jewelry works using filigree and cutting techniques with the main ingredients of silver metal and Trembesi wood. Each work of art contains its own meaning, function and aesthetics. The jewelry is functioned as a complement to womenâ€™s clothing. The jewelry that have been made are necklaces, earrings, bracelets, hairpin, and brooches. The aesthetics of jewelry are described based on Monroe Bardsleyâ€™s theory, namely unity, complexity and sincerity.Â Keywords: lotus plants, jewelry, aesthetics